Circulating Exosomal microRNAs as Biomarkers of Systemic Lupus Erythematosus - Li, Wengen (Clinics (Sao Paulo), 2020)
OBJECTIVES: Many studies indicate that microRNAs (miRNAs) could be potential biomarkers for various diseases. The purpose of this study was to investigate the clinical value of serum exosomal miRNAs in systemic lupus erythematosus (SLE). METHODS: Serum exosomes were isolated from 38 patients with SLE and 18 healthy controls (HCs). The expression of miR-21, miR-146a and miR-155 within exosomes was examined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Using receiver operating characteristic (ROC) curves, we evaluated the diagnostic value of exosomal miRNAs. RESULTS: Exosomal miR-21 and miR-155 were upregulated (p<0.01), whereas miR-146a expression (p<0.05) was downregulated in patients with SLE, compared to that in HCs. The expression of miR-21 (p<0.01) and miR-155 (p<0.05) was higher in SLE patients with lupus nephritis (LN) than in those without LN (non-LN). The analysis of ROC curves revealed that the expression of miR-21 and miR-155 showed a potential diagnostic value for LN. Furthermore, miR-21 (R=0.44, p<0.05) and miR-155 (R=0.33, p<0.05) were positively correlated with proteinuria. The expression of miR-21 was negatively associated with anti-SSA/Ro antibodies (R=−0.38, p<0.05), and that of miR-146a was negatively associated with anti-dsDNA antibodies (R=−0.39, p<0.05). CONCLUSIONS: These findings suggested that exosomal miR-21 and miR-155 expression levels may serve as potential biomarkers for the diagnosis of SLE and LN.